2014
DOI: 10.1002/fsn3.182
|View full text |Cite
|
Sign up to set email alerts
|

Pig feeds rich in rapeseed products and organic selenium increased omega‐3 fatty acids and selenium in pork meat and backfat

Abstract: The concentration of omega-3 fatty acids and selenium (Se) is generally too low in the Western diet. But as the nutrient composition of pork meat and adipose tissue is influenced by the feed given to the animals, the product can be changed to support nutrient demands. Half (297/594) the pigs were given a feed concentrate based on low-glucosinolate rapeseed products (RS), while the other half was fed a traditional concentrate (Contr): The RS feed had an omega-6/omega-3 ratio of 3.6:1, and the Contr feed had a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…This coincides with the linear increase in the elongation index in response to supplementation of BCPO. This observation is consistent with those of Gjerlaug-Enger et al [ 52 ] who observed that dietary rapeseed products enhanced the concentration of C18:3n-3, C20:5n-3 and C22:5n-3 in longissimus dorsi muscle of pork compared with the control diet.…”
Section: Discussionsupporting
confidence: 93%
“…This coincides with the linear increase in the elongation index in response to supplementation of BCPO. This observation is consistent with those of Gjerlaug-Enger et al [ 52 ] who observed that dietary rapeseed products enhanced the concentration of C18:3n-3, C20:5n-3 and C22:5n-3 in longissimus dorsi muscle of pork compared with the control diet.…”
Section: Discussionsupporting
confidence: 93%
“…For chicken, the lipid content of dark meat and light meat averages 28 and 11 g/kg, respectively (21)(22)(23)(24)(25)(26) . The IMF of chicken and pork contains 260-350, 290-460 and up to 200 g/100 g, as SFA, MUFA and PUFA, respectively (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . In beef and lamb, IMF contains 450-480 and 350-450 g/100 g of SFA and MUFA, respectively and up to 50 g/100 g as PUFA, respectively (17,18) .…”
Section: Lipid In Meat From Monogastric and Ruminant Animalsmentioning
confidence: 99%
“…In ruminants, increases in specific FA, including cis-9, trans-11 CLA have been targeted. Most studies have focused on including oilseeds, plant oils, fish oils, marine algae in the diet of pigs (27)(28)(29)(30)(31)(32)(33) , poultry (22,23,(24)(25)(26) , cattle (38)(39)(40)(41) and sheep (42)(43)(44)(45) to alter meat FA composition and content. In ruminants, the use of lipid supplements protected from ruminal metabolism have also been investigated (14,15,46,47) .…”
Section: Nutritional Approaches To Enhance Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most dynamic increase in consumption was recorded for poultry meat, then for pork, beef and meat of other species. Pork meat and its products are a good source of wholesome protein, iron and zinc (Gjerlang-Enger et al, 2015). The meat processing requires the use of salt due to its following functions: shaping the fixed flavor profile, maintaining the color, proper level of protein solubilization strongly associated with the maintenance of own and added water.…”
Section: Introductionmentioning
confidence: 99%